Cacat Kehendak Sebagai Dasar Batalnya Perjanjian - I Ketut Widia; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2022)
Disputes or conflicts are social phenomena that cannot be avoided at all. No society or individual is spared and can be freed from the phenomenon of conflict. Conflict is inevitable. About the causes of the dispute very much. There are disputes that start from problems of love, jealousy, third persons, children, to high-escalation disputes involving many people and society. So far, civil lawsuits have only been based on acts against the law and breaking promises or defaults. This study intends to answer problems related to the cancellation of the agreement based on a cacat kehendak. The problem in question is, can the Cacat Kehendak based on the provisions of Article 1321 of the Civil Code be used as the basis for canceling the sale and purchase of land between Warinah and Nurkhofifah at the Banyuwangi District Court. The second problem is, what are the legal consequences of the cancellation of the sale and purchase of land on the basis of a cacat kehendak between Warinah and Nurkhofifah at the Banyuwangi District Court. This research method is a type of normative legal research. The theory used as a knife for problem analysis is the theory of conflict resolution and the theory of the law of the welfare state. The conclusion of this study is, the sale and purchase transaction agreement based on a cacat kehendak was canceled by the Banyuwangi District Court Judge with Decision Number: 198/Pdt.G/2016/PN.Byw. The legal consequence of the cancellation of the sale and purchase agreement is Warinah as the legal owner of the disputed land again as the owner of the land in question.